2017
DOI: 10.1061/(asce)nm.2153-5477.0000135
|View full text |Cite
|
Sign up to set email alerts
|

How Water-Aggregate Interactions Affect Concrete Creep: Multiscale Analysis

Abstract: Customary micromechanics models for the poroelasticity, creep, and strength of concrete restrict the domain affected by the hydration reaction to the cement paste volume, considering the latter as a thermodynamically closed system with respect to the (chemically inert) aggregate. Accordingly, the famous Powers hydration model appears to be a natural choice for the determination of clinker, cement, water, and aggregate volume fractions entering such micromechanical models. The situation changes once internal cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Mitigation of this problem is the topic of ongoing research [43,44]. Future pertinent multiscale models shall be based on results obtained from innovative early-age testing of the coefficient of thermal expansion [45,46,47], shrinkage [48,49] and creep [50,51,52] of cementitious materials and on corresponding multiscale early-age models for the thermal expansion [53], shrinkage [54] and creep [55,56,57] of cementitious materials. A 16% variation of the thermal expansion coefficient of concrete is expected to result in an increase of the early-age cracking risk by 15%, see Reference [58].…”
Section: Discussionmentioning
confidence: 99%
“…Mitigation of this problem is the topic of ongoing research [43,44]. Future pertinent multiscale models shall be based on results obtained from innovative early-age testing of the coefficient of thermal expansion [45,46,47], shrinkage [48,49] and creep [50,51,52] of cementitious materials and on corresponding multiscale early-age models for the thermal expansion [53], shrinkage [54] and creep [55,56,57] of cementitious materials. A 16% variation of the thermal expansion coefficient of concrete is expected to result in an increase of the early-age cracking risk by 15%, see Reference [58].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the parameter α, which corresponds to the creep compliance at unit time, is found to be largely affected by the compositions of cement paste, degree of hydration and moisture content [6,[17][18][19]. It is also demonstrated by the multiscale studies of cementitious materials that the constituents and microstructures significantly influence the macroscopic viscoelastic behaviour [3,28,31,66,67]. At nanometre scale, Vandamme [2,20] stated that the creep behaviour of the hydrated phases is largely determined by the packing density of C-S-H particles.…”
Section: The Power Law Function Of Creepmentioning
confidence: 99%
“…Notably, the resulting capillary pressure increased virtually linearly with the hydration degree ξ, in the regime ξ > 30%; see [22]. As for mortars and concretes, the self-desiccation-induced capillary underpressure was shown to result in water migration from the open porosity of the aggregates into the cement paste matrix [22]. A similar mechanism is envisaged to reduce the water content of the polymers.…”
Section: Age-dependent Polymer Creep Propertiesmentioning
confidence: 94%
“…Lura et al [62] showed that the internal relative humidity in a cement paste sample with w/c = 0.37 decreased, within the first few days after mixing, from 98% to 92%. Notably, the resulting capillary pressure increased virtually linearly with the hydration degree ξ, in the regime ξ > 30%; see [22]. As for mortars and concretes, the self-desiccation-induced capillary underpressure was shown to result in water migration from the open porosity of the aggregates into the cement paste matrix [22].…”
Section: Age-dependent Polymer Creep Propertiesmentioning
confidence: 94%